Evaluate Retinex Enhancement Method for Captured Images at DifferentCamera Aperture Using Minimum Distance Classifier - Jani, Athraa; Mussaa, Eqbal; Al-Saleh, Anwar; Al-Zuky, Ali (Iraqi Journal of Science, 2024)
In this paper, have been studying the effects of changing camera aperturediameter on image quality, after that had been classified the captured images throughusing Minimum Distance Classification method, after that evaluating the statisticalproperties of the original images and analyzing the results. Next step is enhancingthe original images, and using Multi Scale Retinex algorithm, and then classify theenhanced images and analyze the effects of classification for the enhanced imagesthrough evaluating its statistical properties. We concluded that there was anoticeable improvement in the results, comparing between the classified originalimages with the classified enhanced images, the original image had bad colorappearance, after enhancement it become quite easy to distinguish between differentimage’s classes, there was kind of consistency in the average values of each colorband. The language used in this research is MATLAB language (ver. 2008).